Professionalization of the workforce in television journalism in Imperatriz-MA (Intercom - Brazilian Journal of Communication Sciences, 2023)
In the municipality of Imperatriz, in Maranhão, television is one of the media with the largest coverage and the possibility of broadcasting news. This research aims to understand how the process of professionalization of television journalism professionals took place in the city. For this purpose, a qualitative research was conducted, with data collection through in-depth interviews and content analysis from seven categories. As a result, empirical professionalization is the main form of professionals’ entry into journalistic practice, despite the conventional training of the interviewees. In addition, as advantages, the love of journalism and social contributions to the region. On the other hand, the drop in the requirement of a diploma, low salary and current labor market as negatives points that need to be discussed.